2009
DOI: 10.1016/j.ygcen.2008.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corticosterone pellets on baseline and stress-induced corticosterone and corticosteroid-binding-globulin

Abstract: a b s t r a c tExogenous administration of glucocorticoids is a widely used and efficient tool to investigate the effects of elevated concentrations of these hormones in field studies. Because the effects of corticosterone are dose and duration-dependent, the exact course of plasma corticosterone levels after exogenous administration needs to be known. We tested the performance of self-degradable corticosterone pellets (implanted under the skin) in elevating plasma corticosterone levels. We monitored baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 35 publications
3
69
0
Order By: Relevance
“…In the present study, significant differences in feather CORT content between species were most evident between buzzard and sparrowhawk (both Accipitriformes species) whereas feather CORT concentrations did not differ significantly between barn owls, kestrels and tawny owls. This is consistent with reports that baseline and stress-induced levels of plasma CORT are similar in barn owls and kestrels (Almasi et al, 2012(Almasi et al, , 2013Meijer and Schwabl, 1989;Müller et al, 2009;Stier et al, 2009;Strasser and Heath, 2011).…”
Section: Species Differences In Feather Corticosterone Concentrationsupporting
confidence: 92%
“…In the present study, significant differences in feather CORT content between species were most evident between buzzard and sparrowhawk (both Accipitriformes species) whereas feather CORT concentrations did not differ significantly between barn owls, kestrels and tawny owls. This is consistent with reports that baseline and stress-induced levels of plasma CORT are similar in barn owls and kestrels (Almasi et al, 2012(Almasi et al, , 2013Meijer and Schwabl, 1989;Müller et al, 2009;Stier et al, 2009;Strasser and Heath, 2011).…”
Section: Species Differences In Feather Corticosterone Concentrationsupporting
confidence: 92%
“…corticosterone receptors, corticosterone-binding globulins). Other studies have suggested that these factors may be controlled by baseline levels of corticosterone [42,43], which did not vary among populations at either time of year. Although this study was not designed to elucidate the hormonal mechanisms of exploratory behaviour, previous studies indicate that a relationship between corticosterone release and exploratory behaviour might exist; however, no such withinpopulation relationship was observed.…”
Section: Discussionmentioning
confidence: 85%
“…Commercially available drugs can reduce systemic exposure and toxicity of ingested toxins (Seneca et al 2010). Likewise, the physiological stress response can be suppressed (Gagne et al 1985) or elevated (Muller et al 2009). …”
Section: Future Research Directionsmentioning
confidence: 99%